Soil organic carbon and its labile fractions in the conditions of water erosion on arable land of Chernozems area - Erika Balontayová; Viera Petlušová; Peter Petluš; Juraj Hreško; Štefan Koco (Soil and Water Research, 2024)
The depletion of organic carbon in the topsoil and the reduction of the humic horizon leads to a decrease in soil productivity. This study focussed on evaluating the influence of water erosion on the quantity and quality of organic carbon (OC) in the topsoil. The determination of the differences in the OC with dependence on the soil thickness and the role of the soil texture in a depletion of OC in the humic horizon and its labile fractions were studied in four arable land localities (Haplic Chernozem, HC; Eutric Regosol, ER). The following carbon parameters were included: total organic carbon (TOC), labile carbon oxidisable by KMnO4 (CL), cold and hot water-extractable organic carbons (CWEOCs) and (HWEOCs), respectively. The higher the soil thickness was, the higher the OC contents were at a depth of up to 0.1 m (TOC; r =0.387, P < 0.01; CL; r = 0.266, P < 0.01), which indicates a more pronounced organic and mineral material washing off. This process was more pronounced on the texturally finer HC than the coarser ER soil. In the case of water-extractable organic carbon (WEOC), the vertical movement was dominant, while in the case of CL, the horizontal one was dominant. In the case of erosion, the spatial variability of the OC is not only the result of the erosion-accumulation activities, but also from the proportion of the OC forms. The erosion significantly interferes in the stabilisation mechanisms of organic substances, and even also influences one of the strongest factors - the soil texture.